Atención a la cultura de la diversidad para estudiantes de décimo año, padres de familia y docentes de la escuela de educación básica Adolfo Páez - Milán Chariguamán , Marcia Lorena (2025)
This research addressed the need to address the culture of diversity at the Adolfo Páez Elementary School, targeting tenth-grade students, parents, and teachers. The main objective was to design a socialization workshop that would promote the understanding and appreciation of diversity within the educational community. A non-experimental, cross-sectional design with a qualitative methodology was used, based on exploratory, descriptive, and interpretive research, using surveys, interviews, and observation guides to collect data on perceptions, attitudes, and practices surrounding diversity. The results showed conceptual confusion between cultural diversity and the culture of diversity, as well as prejudices and resistance that affect inclusion. A lack of effective pedagogical strategies for addressing diversity in the classroom was identified. In conclusion, the need to promote a culture of diversity through educational spaces that transform attitudes and improve school coexistence is highlighted. The research culminates with the design of a socialization workshop that seeks to strengthen respect, equity, and inclusion within the institution.